1998
DOI: 10.1016/s0014-5793(98)00470-0
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐mediated regulation of signaling along the p42/44 MAP kinase cascade in vivo

Abstract: The p42/44 mitogen-activated protein (MAP)-kinase cascade is a well-established signal transduction pathway that is initiated at the cell surface and terminates within the nucleus. More specifically, receptor tyrosine kinases can indirectly activate Raf, which in turn leads to activation of MEK and ERK and ultimately phosphorylation of Elk, a nuclear transcription factor. Recent reports have suggested that some members of p42/44 MAP kinase cascade can be sequestered within plasmalemmal caveolae in vivo. For ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
309
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(330 citation statements)
references
References 65 publications
21
309
0
Order By: Relevance
“…Caveolins, the structural components of caveolae, can function as chaperones and provide direct temporal and spatial regulation with numerous cardio-protective signaling molecules via their scaffolding domain including endothelial nitric oxide synthase (eNOS), Src, PKC, Gprotein α, PI3K, and ERK1/2 [16,38,40]. Interestingly, caveolins can inhibit the activity of some of these signaling proteins such as eNOS and ERK1/2 [41][42][43]. However, at the same time caveolins can promote signaling via enhanced receptor-effector coupling or enhanced receptor affinity when caveolins are up regulated or overexpressed [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Caveolins, the structural components of caveolae, can function as chaperones and provide direct temporal and spatial regulation with numerous cardio-protective signaling molecules via their scaffolding domain including endothelial nitric oxide synthase (eNOS), Src, PKC, Gprotein α, PI3K, and ERK1/2 [16,38,40]. Interestingly, caveolins can inhibit the activity of some of these signaling proteins such as eNOS and ERK1/2 [41][42][43]. However, at the same time caveolins can promote signaling via enhanced receptor-effector coupling or enhanced receptor affinity when caveolins are up regulated or overexpressed [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…As caveolin-1 has been previously implicated as a negative regulator of Jak-2/STAT5a signaling and as a tonic inhibitor of the p42/44 MAP kinase cascade (Engelman et al, 1998a), we first evaluated the activation state of these pathways by using a panel of phospho-specific antibody probes. Figure 8A shows that the levels of total STAT5a and phospho-STAT5a remain unchanged in PyMT/ Cav-1 (Ϫ/Ϫ) samples.…”
Section: Loss Of Caveolin-1 Dramatically Up-regulates Cyclin D1 Exprementioning
confidence: 99%
“…The hypercellular lung phenotype observed in Cav-1 null mice also suggests that one or more cell types are experiencing a disruption in cell cycle regulation. Mechanistic insight into the relationship between caveolin-1 and cellular proliferation has been provided by experiments that show that caveolin-1 and the Ras-p42/44 MAP kinase cascade undergo a form of reciprocal regulation: 1) down-regulation of caveolin-1 expression by using an antisense approach leads to constitutive ERK activation (Galbiati et al, 1998); 2) up-regulation of caveolin-1 downregulates p42/44 MAP kinase activity, as measured using an Elk-luciferase reporter system, as well as by using in vitro reconstitution experiments (Engelman et al, 1998a); and 3) down-regulation of p42/44 MAPK activity by treatment of …”
mentioning
confidence: 99%
“…Examples of kinases shown to be inhibited by this association include amongst others the epidermal-and platelet-derived growth factor receptors (EGFR and PDGFR), several members of the ERK1/2 MAP kinase cascade, heterotrimeric G-proteins and src family tyrosine kinases [14][15][16]. Furthermore, several independent studies have demonstrated a reciprocal interaction between the expression of caveolin-1 and activated components of the ERK1/2 MAP kinase signalling pathway [17][18][19][20]. While, caveolin-1 mRNA and protein has been shown to be present in normal human mammary epithelial cells it has also been reported to be greatly reduced or absent in an extensive range of transformed cells derived from human breast cancers [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%